Molecular characteristics of a coxsackievirus A12 strain in Zhejiang of China, 2019 - Linjie Hu; Lu Zhou; Pingping Wang; Hairenguli Maimaiti; Yihan Lu (figshare, 2022)
Abstract Background Enterovirus A (EV-A), such as enterovirus A71 (EV-A71), generally causes hand, foot, and mouth disease (HFMD). However, limited studies focused on uncommon enterovirus serotypes such as coxsackievirus A12 (CV-A12). This study aimed to provide evidence to determine the molecular characteristics of a CV-A12 strain isolated in Zhejiang province, China. Methods In routine surveillance of HFMD, we identified a child case with CV-A12 infection in 2019 in Zhejiang province, China. Enterovirus was examined by using real-time reverse transcription-PCR (qRT-PCR). A partial VP1 sequence was amplified to determine the serotype, and then a full-length CV-A12 genome was sequenced. Nucleotide and amino acid similarity was calculated with those CV-A12 strains available in GenBank. Recombination was detected using RDP 4 and SimPlot. Furthermore, phylogenetic analysis was conducted by using BEAST 1.10, and protein modeling was performed with I-TASSER webserver. Results A full-length CV-A12 genome PJ201984 was isolated in a Chinese child with HFMD. The similarities with complete coding sequences of the CV-A12 strains in GenBank ranged between 79.3–100% (nucleotide) and 94.4–100% (amino acid), whereas it was 88.7–100.0% (nucleotide) and 97.2–100% (amino acid) when excluding the CV-A12 prototype strain Texas-12. In PJ201984, amino acid variations were more divergent in P2 and P3 regions than those in P1; the majority of those variations in VP1 (13/15) and VP4 (7/8) were similar to those documented in recently isolated CV-A12 strains in China. Furthermore, recombination was identified in P2 region, which involved a CV-A5 strain collected in China. Phylogenetic analysis revealed that PJ201984 clustered together with multiple CV-A12 strains isolated in China and the Netherlands during 2013–2018, as compared to another cluster consisting of CV-A12 strains in China and France during 2009–2015. Additionally, protein models of VP1 and VP4 in PJ201984 were well predicted to be similar to VP1 protein of EV-A71 and VP4 protein of coxsackievirus A21, respectively. Conclusions The full-length CV-A12 genome was characterized to have common recombination in P2 region and be phylogenetically related to those CV-A12 strains isolated in recent years, suggesting a continual spread in China. It warrants strengthening the routine surveillance for uncommon enterovirus serotypes, particularly on possible recombination and variation.
Keywords: Biochemistry; Medicine; Microbiology; Genetics; Molecular Biology; Physiology; Biotechnology; Evolutionary Biology; Environmental Sciences not elsewhere classified; Chemical Sciences not elsewhere classified; Ecology; Biological Sciences not elsewhere classified; Infectious Diseases